The Influence Of Digital Marketing Strategy On The Interest In Buying Miemu In Surakarta City - Nurhaliza, Cut; Sholahuddin, Muhammad (Jurnal Economic Resource, 2024)
Marketing strategy is a type of plan in the field of marketing. In general, marketing is a social process in which individuals or groups obtain what they need or want by creating products or values ​​and exchanging them with other people or groups. The purpose of is to show research results that are relevant to the achievement of the results of the Influence of Digital Marketing Strategy on Purchase Interest in Miemu in Surakarta City. This research was conducted using a quantitative approach with a data collection method through a questionnaire distributed online to respondents in Surakarta City. The results of this study can be concluded that the results of the analysis show that there is a positive correlation between digital marketing strategies and purchase interest in Mie Mu products. Although not all factors that influence purchasing decisions can be explained by digital marketing variables, this strategy makes a significant contribution to increasing the attractiveness of the product in the eyes of consumers. This indicates that investing in digital marketing, such as through social media and creative content, is the right step to increase Mie Mu sales.